Malaria vaccine study site in Irian Jaya, Indonesia: Plasmodium falciparum incidence measurements and epidemiologic considerations in sample size estimation. - Jones, T; Baird, J; Bangs, M; Annis, B; Purnomo; Basri, H; Gunawan, S; Harjosuwarno, S; McElroy, P; Hoffman, S (1994)
Malaria epidemiologic and entomologic studies were performed during both the high transmission and low transmission seasons to characterize the Plasmodium falciparum malaria transmission at a proposed malaria vaccine trial site in Irian Jaya, Indonesia. The study population consisted of two subsets: native Irianese men with lifelong exposure to malaria and transmigrants who arrived from a nonmalarious area 2.5 years before the start of the study. All subjects received a radical cure for malaria and were then monitored weekly by blood film. Both P. falciparum malaria attack rates and incidence densities were calculated; transmigrants had a significantly higher rate (P = 0.003) than the Irianese during the low transmission season study (20-weeks long) but not during the high transmission season study (12-weeks long). Lack of exposure-induced immunity left the transmigrants at a minimum 17-25% greater relative risk of becoming parasitemic compared with the Irianese during the low transmission season study. During the high transmission season study, 50% of the transmigrants were P. falciparum positive by week 6 and 50% of the Irianese by week 9. During the low transmission season, 50% of the transmigrants were positive by week 10 and 43% of the Irianese were positive by week 17. Entomologic studies showed that Anopheles koliensis was the predominant vector (> 98% of anopheline catch). Entomologic inoculation rates for P. falciparum were 0.018 and 0.39 infective bites/person/night for the low and high transmission seasons, respectively. New P. vivax cases represented between 16% and 42% of all initial malaria cases.(ABSTRACT TRUNCATED AT 250 WORDS)